Grey Systems Theory Time Series Prediction applied to Road Traffic Safety in Germany. Issue 3 (2016) - René S., Hosse; Becker, U.; Manz, H.
Abstract: Although Road Traffic Safety in Germany has improved over the last four decades, nowadays more than 3000 people per year die in a car accident. Due to that the European Union signed the Vision Zero aiming to zero deaths until 2020. This goal seems hard to achieve investigating latest data on road traffic accidents. Furthermore it is yet unclear what provisions should be undertaken by government or industry to improve safety. This research applies a Grey Systems Theory MGM(1, 4) in order to predict the development of road traffic accidents in Germany until 2025 based on the market diffusion of electronic stability program (ESP). Grey Systems Theory has shown impressive results in various applications and has the benefit to correlate multiple time series. The findings exemplify that only minor improvements until 2025 are to expect, having around 2000 fatalities per year, and more provisions must be made to achieve the Vision Zero.